Analysis of the Impact of Foreign Direct Investment and Foreign Labor on the Economy of NTB - Lengkong, Dita Purnamasanti; Wahyunadi, Wahyunadi (Journal of Finance and Business Digital, 2024)
Economic progress is the main sign that shows the development and prosperity of a region. Every country certainly expects rapid economic growth to improve the welfare of its people. Economic growth is a consequence of various activities that support economic development This study aims to analyze the impact of Foreign Direct Investment Foreign Investment and Foreign Labor on the NTB economy. This research uses secondary data. Using descriptive and associative quantitative methods with multiple linear regression analysis tools (time series data regression) and data sourced from the Central Bureau of Statistics, Manpower and Transmigration Office using the eviews12 program. The results of this study indicate that the Foreign Investment variable partially has a significant positive effect on economic growth while the Foreign Labor variable has a positive but insignificant effect. And simultaneously the variables of Foreign Labor and Foreign Investment have a significant and simultaneous effect on economic growth.